The Role of Digital Technology in the Development of Small and Medium Enterprises (SMEs) in Makassar - Halim, Nur; Agus; Mahmuddin (Cita konsultindo, 2025)
This study aims to analyze the role of digital technology in the development of Small and Medium Enterprises (SMEs) in Tidung, Makassar. In today's digital era, the adoption of digital technologies such as online marketing, e-commerce, and social media has become a crucial factor in driving the growth of SMEs, improving operational efficiency, expanding market reach, and fostering product and service innovation. This research employs a descriptive qualitative approach to deeply understand the utilization of digital technology by SMEs in Tidung, focusing on the benefits gained and the challenges faced in the digitalization process. The findings reveal that although SMEs in Tidung experience significant benefits from adopting digital technologies, such as increased market visibility and operational efficiency, challenges such as limited resources, infrastructure, and low digital literacy remain major obstacles. Therefore, enhancing digital literacy and improving infrastructure support are necessary to accelerate digitalization among SMEs. This study is expected to provide valuable insights for policymakers and SME practitioners to optimize the use of digital technology to achieve sustainable growth and enhance their contribution to the local and national economy.